Internalisasi Nilai-Nilai Pendidikan Agama Islam melalui Metode Pembiasaan Siswa Madrasah Ibtidaiyah - Dede Abdul Hakim (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Education is an important part of human life, education (especially Islam) with its various patterns is oriented towards providing provision for humans (students) to achieve happiness in the world and the hereafter. Religious education is God's command and is a manifestation of worship to Him. This theory attaches great importance to the input in the form of a stimulus and the output of the hadith in the form of a response. In the learning process this input can be in the form of props, pictures, or certain ways to help the learning process. This study aims to describe what Islamic religious education values ??are internalized. The results of this study in applying the values ??of Islamic Religious Education to students of MI Al-Hidayah and MI An-Nur Bandung Regency using the habituation method is considered quite good and effective. The use of this habituation method is carried out in the classroom through the Islamic Religious Education material being taught. While outside the classroom the students are accustomed to praying in congregation, praying dhuha and having good morals. In its implementation, it still requires personal awareness of praying in congregation, praying dhuha and having good morals. In its implementation, students still need personal awareness with guidance and supervision by teachers and parents at home.